Comparación del crecimiento de cerdos Duroc-Jersey cruzados y puros alimentados con raciones simples y raciones completas - Jarquín, R. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Fourteen purebred Duroc Jersey pigs, and sixteen crossbred pigs were used in Guatemala for comparison of performance when fed a local (simplified) ration and a more complete imported one, in order that limitations of rations and genetic potential could be evaluated. The results showed: The average daily gains of all purebred pigs, disregarding ration treatments, were superior to the average daily gain of the crossbred pigs. The average daily gains of the purebred pigs receiving the local ration and the purebred pigs receiving the imported ration were not significantly different. The average daily gains of all pigs, disregarding breeds, receiving the imported ration were superior to the average daily gain of pigs receiving the local ration. The average daily gains of the crossbred pigs when receiving the imported and the local rations were not significantly different. The trend in the growth results of the crossbred pigs fed the local ration indicate that if fed a good ration they can do as well as purebred pigs fed the local ration. The overall results definitely indicate that with an improvement in ration a satisfactory response can be expected from the crossbred pigs; possibly the addition of antibiotics would be helpful in this regard. Under tropical conditions these data indicate that even with locally available simplified rations the use of purebred boars on native sows may be an efficient way for increasing pork production